An English Teachers’ Perspectives on Differentiated Instruction in ‘Kurikulum Merdeka’: A Case Study in SMA Kabupaten Solok - Mairoza , Destri; Roza, Welya; Samanhudi, Udi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
This research aimed to find out the perspectives that SMA English teachers in Kabupaten Solok have on Differentiated Instruction, the implementation, and the challenges. This research was a qualitative case study. Data collection was based on questionnaires, in-depth interviews, document analysis, and participant observation. Informants who became data sources in this study were selected based on purposive sampling, namely teachers who teach in grade X (Fase E), have more than 10 years of English teaching experience, and were willing to become informants. The data obtained was that informants showed their understanding of Differentiated Instruction from the process of self-learning through PMM and peer discussions. However, in terms of planning on the teaching modules prepared, not all informants have clear planning on Differentiated Instruction. Similarly, it was found during classroom observations that not all informants implemented Differentiated Instruction by the required aspects and considerations. It could be concluded that the informants have explained their understanding of Differentiated Instruction theoretically. However, this was not the case when it came to planning the teaching module and implementing it in the classroom. Some informants showed confusion and incomprehension in the implementation of Differentiated Instruction in the lesson planning and the classroom